Smart Phones and Brand Equity: a Study of Malaysian Consumer Buying Behavior - Zandi, Gholam Reza; Aslam, Ayesha; Nasir, Muhammad Umar; Zhang, Yajing (International Journal of Engineering and Technology, 2018)
This research is conducted in Malaysia focusing on the university students who are getting fond of using the smartphones as a status symbol. The region for data collection is not the entire Malaysia but only the specific areas of Malaysia. In which the capital city Kuala Lumpur, Petaling Jaya and Subang are included. The respondents are the university students of Malaysia. Research sample has been chosen approximately 300 students by different universities. The mode of data collection is questionnaire. Questionnaire is consisted on 30 questions regarding to the independent and dependent variable both with each dimensions. Research is quantitative and after data collection, the analysis has been performed on SPSS. The entire statistical test performed on the collected data and researcher comes up with the conclusion that all the brand equity dimensions have positive and significant relationship with consumer buying behavior. All the customers are more concerned about the brands with which they are attached and they are going to buy. The most effective dimension of brand equity is perceived quality.Â The perceived quality of the brand is directly related to the level of satisfaction of the customers and for the repeating of the purchase, the actual quality of the band should be more or equal to the perceived quality of the customers. The recommendations for future research are based upon the cultural, social, personal and psychological perspectives.